Adhesive joints for vegetal natural fibres reinforced composites - José L. Esteves (2007)
The increased interested for the utilisation of natural fibres, to produce new ecologicalcomposites materials, need the analysed and development of joining processes to assemble ofdifferent parts made with these materials.In this work we present the mechanical characterisation of adhesive single lap joints for the joiningof sisal fibres reinforced composite materials with an epoxy matrix.We made experiences with different surface treatments of the fibres, with the objective ofincreasing the adhesion between the fibres and the matrix, and consequently to improve mechanicalbehaviour of the composite material and the adhesive joint.A brief description of the production and test setups of the composite materials and the adhesivejoints is made.An analytical and numerical calculation of the behaviour of the adhesive joints is presented andcompared with the experimental results.